Research Trends on Babinsa (Village Supervisory Non-Commissioned Officers): Scientific Perspectives, Study Focus, and Implications - Hiras M. S. Turnip (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study analyses research trends on Babinsa (Bintara Pembina Desa/Village Management Senior NCO) based on fifty-two academic publications from 2013 to March 2025. The study aims to identify topic trends, dominant disciplines, temporal distribution, and research methodologies. Findings reveal a shift from a focus on security and public order to socio-economic empowerment, cross-sectoral collaboration, and technology utilization. Research is dominated by the Social-Political Sciences discipline and qualitative approaches. Gaps are found in regulatory aspects, long-term evaluation, and community-based perspectives. This study provides insights to support policymaking and enhance the effectiveness of Babinsa's role in society.